2004
DOI: 10.1302/0301-620x.86b7.13747
|View full text |Cite
|
Sign up to set email alerts
|

Regional regenerative potential of meniscal cartilage exposed to recombinant insulin-like growth factor-I in vitro

Abstract: It is well recognised that meniscal tears situated within the inner, avascular region do not heal. We investigated the potential effect of insulin-like growth factor-I (IGF-I) in promoting regeneration of meniscal tissue in the inner, middle and outer zones of the meniscus. Sheep menisci were harvested and monolayer cell cultures prepared. Various concentrations of IGF-I were used in the presence or absence of 10% fetal calf serum (FCS). We measured the uptake of radioactive thymidine, sulphur, and proline to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Furthermore, census data indicates a significant increase in the longevity of the general population; thus, the prevalence of meniscal disorders will therefore increase in the forthcoming decades requiring effective solutions to such musculoskeletal conditions. Modern approaches using tissue engineering (Peretti et al 2004;Buma et al 2004;Tumia and Johnstone 2004b) and novel biological agents to stimulate meniscal repair may represent possible therapeutic intervention strategies worthy of further evaluation for the treatment of such problematic clinical disorders. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, census data indicates a significant increase in the longevity of the general population; thus, the prevalence of meniscal disorders will therefore increase in the forthcoming decades requiring effective solutions to such musculoskeletal conditions. Modern approaches using tissue engineering (Peretti et al 2004;Buma et al 2004;Tumia and Johnstone 2004b) and novel biological agents to stimulate meniscal repair may represent possible therapeutic intervention strategies worthy of further evaluation for the treatment of such problematic clinical disorders. …”
Section: Discussionmentioning
confidence: 99%
“…Based on the blood and nutrition supply, the meniscus is divided into three zones: a red zone, a white zone, and a red-white zone [24]. Fibrochondrocytes in different zones of the menisci display different morphology correlating with their stress and nutritional microenvironment [28]. In primary monolayer cell cultures, the meniscal fibrochondrocytes are a mixture of phenotypes, oval-or spindle-shaped cells that normally exist in the superficial layer of the meniscus, and roundshaped cells which are found predominantly in the deep layer.…”
Section: Introductionmentioning
confidence: 99%
“…Tumia and colleagues presented a series of experiments in which they showed that meniscal cells from the inner avascular zone could be stimulated to proliferate when exposed to IGF [41], FGF [42], and PDGF-AB [43]. Platelet derived growth factor, in particular was shown to stimulate an 8-fold increase in cell proliferation and a 4-fold increase in matrix production in vitro [43].…”
Section: Cell Biology and Meniscal Healing: Cytokines And Growth Factorsmentioning
confidence: 99%